Beispiel Nr: 04
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 9 x -2 y =1\\ -3 x -3 y = -7 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 9 x -2 y =1\\ II \qquad -3 x -3 y = -7 \\ \text{I nach y auflösen}\\ 9 x -2 y =1 \\ 9 x -2 y =1 \qquad /-9 x\\ -2 y =1 -9 x \qquad /:\left(-2\right) \\ y =-\frac{1}{2} +4\frac{1}{2} x \\ \text{II nach y auflösen}\\ -3 x -3 y =-7 \\ -3 x -3 y =-7 \qquad /+3 x\\ -3 y =-7 +3 x \qquad /:\left(-3\right) \\ y =2\frac{1}{3} -1 x \\ \text{I = II}\\ -\frac{1}{2} +4\frac{1}{2} x =2\frac{1}{3} -1 x \qquad /-4\frac{1}{2} x /-2\frac{1}{3} \\ -\frac{1}{2}-2\frac{1}{3} =-1 x -4\frac{1}{2} x \\ -2\frac{5}{6} =-5\frac{1}{2} x \qquad /:\left(-5\frac{1}{2}\right) \\ x=\frac{17}{33} \\ \text{x in I}\\ y =-\frac{1}{2} +4\frac{1}{2} \cdot \frac{17}{33} \\ y=1\frac{9}{11} \\ L=\{\frac{17}{33}/1\frac{9}{11}\} \end{array} & \begin{array}{l} I \qquad 9 x -2 y =1\\ II \qquad -3 x -3 y = -7 \\ \text{I nach x auflösen}\\ 9 x -2 y =1 \\ 9 x -2 y =1 \qquad /+2 y\\ 9 x =1 +2 y \qquad /:9 \\ x =\frac{1}{9} +\frac{2}{9} y \\ \text{II nach x auflösen}\\ -3 x -3 y =-7 \\ -3 x -3 y =-7 \qquad /+3 y\\ -3 x =-7 +3 y \qquad /:\left(-3\right) \\ x =2\frac{1}{3} -1 y \\ \text{I = II}\\ \frac{1}{9} +\frac{2}{9} y =2\frac{1}{3} -1 y \qquad /-\frac{2}{9} y /-2\frac{1}{3} \\ \frac{1}{9}-2\frac{1}{3} =-1 y -\frac{2}{9} y \\ -2\frac{2}{9} =-1\frac{2}{9} y \qquad /:\left(-1\frac{2}{9}\right) \\ y=1\frac{9}{11} \\ \text{y in I}\\ x =\frac{1}{9} +\frac{2}{9} \cdot 1\frac{9}{11} \\ x=\frac{17}{33} \\ L=\{\frac{17}{33}/1\frac{9}{11}\} \end{array} \end{array} $